CALCULATION OF GROWTH RATES AND COMPOSITIONS OF NANOLAYERS InXGa1-XAs ON A InP SUBSTRATE USING A 3D MODEL OF A HORIZONTAL MOVPE REACTOR - A. A. Gorskiy; L. B. Berliner; E. V. Titova (Тонкие химические технологии)
A three-dimensional (3D) detailed heat, mass and momentum transfer model was constructed to describe the thermal behavior, fluid dynamics and the diffusion in a horizontal metal-organic vapor-phase epitaxy (MOVPE) reactor with a rectangular section and a rotated substrate keeper with inductive heating used for numerical studying to obtain optimum conditions for the growth process and to calculate the growth rate and the composition of InxGa1-xAs nanolayers.